Polymeric Stabilization of Nano‐Scale HMX Suspensions During Wet Milling. Issue 5 (1st April 2019) - Doukkali, Mouhcine A.; Gauthier, Eric; Patel, Rajen B.; Stepanov, Victor; Hadim, Hamid
Abstract: The focus of this paper is to investigate the polymeric stabilization of cyclotetramethylene tetranitramine (HMX) suspensions using polyvinylpyrrolidone (PVP). The PVP adsorption on HMX surface was studied using zeta potential measurements, which revealed that the shorter PVP polymer chain (lesser molecular weight) adsorbed better than the longer one (greater molecular weight). This study also showed that the solvent dramatically affects the PVP adsorption. A turbidity test was conducted, showing that lower molecular weight PVP offers better stability. This stability is enhanced by increasing the ethanol concentration. The depletion mechanism was responsible for HMX stabilization with ethanol. Finally, a milling study was conducted to compare the HMX with and without a stabilization mechanism. This study indicated that PVP in 50 % water/50 % ethanol was able to stabilize HMX by depletion and reduce the size to 180 nm within 10 minutes of milling. Strong aggregation was observed for HMX milled in the absence of the stabilization mechanism. The stabilization techniques discussed in this study appeared to lead to a shorter processing time and a more efficient milling process when utilized. Under comparable milling conditions, a particle size of 180 nm could be achieved with stabilization compared to 500 nm without. Such a dramatic improvement of the milling process bodes well for future nanoHMX production, as well as that of similar materials. Abstract :